Impact of GOLD Retrieved Thermospheric Temperatures on a Whole Atmosphere Data Assimilation Model. Issue 1 (18th January 2021) - Laskar, F. I.; Pedatella, N. M.; Codrescu, M. V.; Eastes, R. W.; Evans, J. S.; Burns, A. G.; McClintock, W.
Abstract: The present investigation evaluates the assimilation of synthetic data which has properties similar to actual Global‐scale Observations of the Limb and Disk (GOLD) level‐2 (L2) temperatures and other conventional lower atmospheric observations. The lower atmospheric and GOLD L2 temperature ( T disk ) are assimilated in the Whole Atmosphere Community Climate Model with thermosphere‐ionosphere eXtension using Data Assimilation Research Testbed. It is found that inclusion of the GOLD T disk improves the forecast root mean square error (RMSE) and bias by 5% and 71%. When compared to lower atmosphere only assimilation, the improvements in RMSE and bias are 20% and 94%. An investigation of the global diurnal westward‐propagating wavenumber 1 (DW1) and local diurnal tidal characteristics shows that inclusion of the GOLD temperatures improves the DW1 by about 8% and diurnal tide by more than 17%. Larger percentage improvements in the tides are seen in the lower thermosphere. Considerable improvements in the model state are also seen at times and locations where there are no GOLD observations available. These results and the background data assimilation procedure are presented here, which demonstrate that GOLD thermospheric temperature is an excellent data set that can be used for thermospheric assimilation studies and operational purposes. Plain Language Summary: A perfect numerical model simulation of the Earth is the one that can reproduce the whole atmosphere‐ionosphere‐thermosphere (AIT) system at any point of time. With time, the numerical models are evolving and the simulation capabilities are enhanced with new understanding of the AIT system dynamics, but they are still far from perfect. On the other hand, if one can measure any parameter or state of the AIT system at any point of time then the numerical models will be of no use. In the absence of both the above highly ambitious extreme possibilities, both the state‐of‐the‐art model capabilities and AIT measurements can be combined in a data assimilation framework to study the dynamics and to better understand the AIT system. The present investigation evaluates GOLD mission level‐2 disk temperatures and finds that they can significantly improve the thermospheric assimilation capability. Key Points: Synthetic level 2 Global‐scale Observations of the Limb and Disk temperatures are assimilated and tested in WACCMX + DART The assimilation improves root mean square error and bias in thermospheric temperature by 5%–20% and 71%–94% Diurnal westward‐propagating wavenumber 1 and local diurnal tide are improved by about 7% and 17%, respectively, at thermospheric altitudes